2012
DOI: 10.1108/03090561211259961
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneous effect of WOM on product sales: why the effect of WOM valence is mixed?

Abstract: Purpose -Previous literature on WOM has consistent findings on the positive and significant effect of WOM volume on product sales, but the literature on WOM valence has been mixed. In this study, the authors aim to explain the reason for the mixed effect of WOM valence on product sales by considering heterogeneous characteristics of products, especially in the movie market, by segmenting products into mainstream and non-mainstream movies. Design/methodology/approach -This study uses empirical data from the mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 39 publications
1
46
1
1
Order By: Relevance
“…For example, decision-making of audiences regarding local and U.S. films seems to vary when we consider differences in marketing budget and channels between local and Hollywood distributors (Walls, 1997;McKenzie, 2009;Yang, Kim, Amblee, & Jeong, 2012). Deciding whether to see a local film would theoretically take more time because the amount and type of information available about such movies is limited during the prerelease period compared with imported movies.…”
Section: Revenue Decay and Movie Qualitymentioning
confidence: 94%
“…For example, decision-making of audiences regarding local and U.S. films seems to vary when we consider differences in marketing budget and channels between local and Hollywood distributors (Walls, 1997;McKenzie, 2009;Yang, Kim, Amblee, & Jeong, 2012). Deciding whether to see a local film would theoretically take more time because the amount and type of information available about such movies is limited during the prerelease period compared with imported movies.…”
Section: Revenue Decay and Movie Qualitymentioning
confidence: 94%
“…Purchase decisions may be influenced by person-related factors, but also factors such as price, brand, product information, product quality and value, advertising, promotion, or the reference price (e.g., Chang and Wildt 1994). For example, increased marketing efforts can diminish the effect of valence (Yang et al 2012). To control for some of those variables we included price in our analysis, but future studies should investigate how price influences the effects of online reviews.…”
Section: Limitations Alternative Explanations Future Research and mentioning
confidence: 99%
“…Previous literature has shown that online review volume has a quantitatively measurable impact on product sales (Davis and Khazanchi, 2008;Duan et al, 2008;Liu, 2006;Lu et al, 2013). It is believed that the increased consumer product awareness caused by online review volume leads to higher sales (Liu 2006;Yang et al, 2012). For example, Lu et al (2013) found that online review volume has led to an increase in restaurant sales.…”
Section: Online Review Volumementioning
confidence: 99%
“…Online review valence refers to the nature of e-UGC content, which is usually presented in the form of an evaluation score which can be positive, negative or mixed (Yang et al, 2012). Although previous research has found a persuasive effect of online review valance on consumer purchase decision making (Cheung and Thadani, 2012), there is no consensus about the effect of online review valence on sales.…”
Section: Online Review Valencementioning
confidence: 99%
See 1 more Smart Citation